2006
DOI: 10.1002/art.22040
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of osteoarthritis‐like changes in the joints of mice deficient in type IX collagen

Abstract: Objective. To examine the pathogenetic mechanisms of osteoarthritis (OA)-like changes in Col9a1 ؊/؊ mice, which are deficient in type IX collagen.Methods. Knee joints and temporomandibular joints (TMJs) from Col9a1 ؊/؊ mice and their wild-type (Col9a1 ؉/؉ ) littermates were examined by light microscopy. Immunohistochemical staining was performed to examine the expression of matrix metalloproteinase 3 (MMP-3) and MMP-13, degraded type II collagen, and the discoidin domain receptor 2 (DDR-2) in knee joints. Cart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 39 publications
6
105
1
1
Order By: Relevance
“…In contrast to the TSP-null mouse strains, previous studies of type IX collagen knockout mice showed earlyonset osteoarthritis, 31,43 less MATN3 incorporation into 46 and slower fracture repair. 47 We observed similar findings and, in addition, found wider growth plates and significant limb shortening at 1 month of age.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast to the TSP-null mouse strains, previous studies of type IX collagen knockout mice showed earlyonset osteoarthritis, 31,43 less MATN3 incorporation into 46 and slower fracture repair. 47 We observed similar findings and, in addition, found wider growth plates and significant limb shortening at 1 month of age.…”
Section: Discussionmentioning
confidence: 61%
“…Existing spontaneous mouse models of OA are commonly limited by the time to develop a full phenotype. For example, STR/ORT (39), collagen type IX (COL9A1)-deficient, and heterozygous Col11a1 chondrodysplasia mice each take >6 mo to develop robust disease, although subtle changes are present in the latter two models at 3 mo of age (31,40). Mice lacking NFATc2 alone develop OA, although also with slow kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of Col2a1, a major organic component of cartilage matrix, was also up-regulated, suggesting that cartilage matrix turnover is hyperdynamic, perhaps in an effort to compensate for catabolism. Absence of type IX collagen in Col9a1 −/− mice results in age-dependent OA-like changes in mice, and Col9a1 expression was moderately reduced in Nfatc1 col2 Nfatc2 −/− mice (31). Inducible deletion of sex-determining region Y (SRY)-Box 9 (Sox9) in adult mice is associated with proteoglycan depletion at articular surfaces, and Sox9 expression was also reduced (32).…”
Section: Molecular Characterization Of Cartilage Matrix Degradation Inmentioning
confidence: 99%
“…Genotyping procedures of Col9a1 -/-and cho/+ mice have been described previously (8,10). Col9a1 -/-, cho/+ and wild-type mice were separated and maintained under a 12-hour lighting schedule (12 hours with light and 12 hours without light).…”
Section: Genotyping Of Col9a1 -/-And Cho/+ Micementioning
confidence: 99%
“…It has been reported that the expression of MMP-3 and MMP-13 is increased in TM joints of OA patients (4,5). We have been investigating the pathogenesis of OA using two murine mutant models: type IX collagen-deficient (Col9a1 -/-) and type XI collagen-haploinsufficient (heterozygous chondrodysplasia, cho/+) mice (6)(7)(8). Both mutant mouse strains developed normally, but exhibited age-dependent OA-like changes in knee and TM joints starting at 3 months of age.…”
Section: Introductionmentioning
confidence: 99%